The Importance of Vibronic Coupling for Efficient Reverse Intersystem Crossing in Thermally Activated Delayed Fluorescence Molecules - Gibson, Jamie; Monkman, Andrew P.; Penfold, Thomas J. (Chemphyschem, 2016)
Factors influencing the rate of reverse intersystem crossing (krISC) in thermally activated delayed fluorescence (TADF) emitters are critical for improving the efficiency and performance of third‐generation heavy‐metal‐free organic light‐emitting diodes (OLEDs). However, present understanding of the TADF mechanism does not extend far beyond a thermal equilibrium between the lowest singlet and triplet states and consequently research has focused almost exclusively on the energy gap between these two states. Herein, we use a model spin‐vibronic Hamiltonian to reveal the crucial role of non‐Born‐Oppenheimer effects in determining krISC. We demonstrate that vibronic (nonadiabatic) coupling between the lowest local excitation triplet (3LE) and lowest charge transfer triplet (3CT) opens the possibility for significant second‐order coupling effects and increases krISC by about four orders of magnitude. Crucially, these simulations reveal the dynamical mechanism for highly efficient TADF and opens design routes that go beyond the Born‐Oppenheimer approximation for the future development of high‐performing systems. A model spin‐vibronic Hamiltonian is used to reveal the crucial role of non‐Born‐Oppenheimer effects in determining the rate of reverse intersystem crossing (krISC). The authors demonstrate that vibronic (nonadiabatic) coupling between the lowest local excitation triplet and lowest charge transfer triplet opens the possibility for significant second‐order coupling effects and increases krISC by about four orders of magnitude.